(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article examines the role of technology education in developing students’ independent thinking and professional skills in contemporary school systems. The problem is not merely whether students can use devices or reproduce procedural tasks, but whether the technology subject can become a pedagogical space in which learners plan, test, revise, evaluate, create, cooperate, and make informed decisions that connect school knowledge with real vocational pathways. The study is designed as an analytical review and conceptual synthesis in the IMRaD tradition. Its source base combines international policy frameworks and recent scholarly research on technology-enhanced learning, student agency, critical thinking, computational thinking, self-regulated learning, vocational preparation, and future-ready competencies. The analysis is guided by the proposition that technology education occupies a distinctive place in the curriculum because it unites cognitive, practical, ethical, and productive dimensions of learning more directly than many purely academic subjects. Unlike narrowly instrumental computer use, a robust technology subject engages learners in problem framing, design reasoning, tool selection, prototyping, documentation, reflection, and presentation to authentic audiences. The review identifies six core mechanisms through which the subject contributes to independent thinking and professional formation: design-based inquiry, iterative problem solving, self-regulation and metacognition, collaborative production, transfer to real work contexts, and technological awareness linked to ethics and responsibility. The findings indicate that the formative power of the subject depends less on the presence of devices than on the organization of pedagogical tasks, assessment culture, teacher expertise, and the degree of connection between classroom production and meaningful social or occupational problems. When technology education is reduced to demonstration, copying, or fragmented tool training, its developmental potential declines sharply. When it is organized around purposeful design tasks, reflection, documentation, and applied problem solving, it becomes a strong medium for cultivating agency, career imagination, adaptability, and practice-oriented competence. The article concludes that technology education should be treated as a strategic component of general education and career development policy, not as a secondary auxiliary course. Curriculum modernization must therefore focus on authentic projects, interdisciplinary integration, safety and ethics, reflective assessment, and teacher preparation capable of balancing technological fluency with human judgment. The article offers a conceptual model and practical implications for schools seeking to make technology education a driver of student autonomy, employability, and lifelong learning.